2004
DOI: 10.1086/423868
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding Depression inNigella degenii(Ranunculaceae): Fitness Components Compared with Morphological and Phenological Characters

Abstract: We have compared selfed and outbred offspring from individual plants of the annual plant Nigella degenii to examine patterns of inbreeding depression in two direct components of fitness (flower number and pollen viability) and a number of morphological or phenological characters for which the optimal phenotype may be habitat specific. Selfing lowered flower number, plant height, flower size, and pollen viability and caused a shift toward later germination and flowering dates. There was no significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 37 publications
6
18
1
1
Order By: Relevance
“…It has been shown that selfing is followed by a decline in male reproductive capacity, affecting both the amount of pollen produced (Carr and Dudash, 1997;Goodwillie and Knight, 2006) and its viability (Willis, 1993;Carr and Dudash, 1997;Ellmer and Andersson, 2004), and this was confirmed in the present study. This negative effect has important implications for the maintenance of populations and for the species' colonization capacity.…”
Section: Effect Of Id In the First Stages Of The Life Cycle Of Anagyrsupporting
confidence: 88%
See 1 more Smart Citation
“…It has been shown that selfing is followed by a decline in male reproductive capacity, affecting both the amount of pollen produced (Carr and Dudash, 1997;Goodwillie and Knight, 2006) and its viability (Willis, 1993;Carr and Dudash, 1997;Ellmer and Andersson, 2004), and this was confirmed in the present study. This negative effect has important implications for the maintenance of populations and for the species' colonization capacity.…”
Section: Effect Of Id In the First Stages Of The Life Cycle Of Anagyrsupporting
confidence: 88%
“…Thiele et al (2010) proposed the lower effect of ID in floral traits than in fitness traits could be because selection acts more strongly on flowers than on fitness or because selection acting on floral traits may be stabilizing, in contrast to selection on fitness traits that likely is directional. Indeed, previous studies showed ID has hardly any effect on flower size or on the floral pieces such as sepals or petals (Ellmer and Andersson, 2004;Thiele et al, 2010).…”
Section: Effect Of Id In the First Stages Of The Life Cycle Of Anagyrmentioning
confidence: 97%
“…A meta-analysis of inbreeding depression estimates for different trait types in animals provided further support (DeRose and Roff 1999). In contrast, Ellmer and Andersson (2004) found no significant difference in the degree of inbreeding depression in traits closely related to fitness compared to morphological and phenological characters in the annual plant Nigella degenii. Nevertheless, they did report a trend towards greater reduction in fitnessrelated traits, and their sample size was small, with only two fitness-related traits assessed.…”
Section: Introductionmentioning
confidence: 89%
“…The effects of inbreeding have also shown to vary considerably among different types of traits (e.g., morphological versus fitness-related traits), and even among different components of complex traits such as fitness (Ouborg and Van Treuren 1995;Fry et al 1998;Margulis 1998;Roff 1998;DeRose and Roff 1999;Ellmer and Andersson 2004). There has been considerable debate regarding the genetic basis of inbreeding depression.…”
Section: Drift Effects On Multiple Trait Componentsmentioning
confidence: 99%